The Relationship Between Lymph Node Staging and Tumor SUVmax in NSCLC - Balcil, T. A.; Komek, H.; Cengiz, M.; Kaya, H. (Springer, 2012)
[Abstract Not Available]
25th Annual Congress of the European-Association-of-Nuclear-Medicine (EANM) -- OCT 27-31, 2012 -- Milan, ITALY